Awareness of implementation building information modelling (BIM) in construction industries - Siti Nursyazwani, Kahapah (2015)
Building Information Modeling (BIM) is a technology that is currently emerging in the construction industry. BIM is defined as a modeling technology and associated set of process to produce communicate, and analyse building models throughout the projects lifecycle. Nevertheless, in Malaysia show that the adoption of BIM is still early stage because only a few companies that implementing BIM in their organization. Therefore, the purpose of this study is to identify the level awareness of implementation BIM among project manager, and to identify the barrier of BIM implementation in construction industry. Questionnaire have been used to obtain the data. There are 65 sets of questionnaire have been collected back. Consequently, result of this study stated that most of the project manager in Kelantan are aware on the implementation of BIM in construction industry. The main barriers for implementing the BIM are lack of training and respondents also said that BIM is expensive to implement in their organization.